DEVELOPMENT OF EVALUATION MEDIA BASED ON WORDWALL GAMES INTEGRATED WITH GOOGLE SITES ON SPLDV MATERIAL - Mardiyah, Ainun Naumahatun; Murniasih, Tatik Retno; Rahaju, Rahaju (Universitas Tanjungpura, 2025)
This study aims to determine the validity and practicability of evaluation mediabased on wordwall games integrated with google sites developed using theADDIEmodel.The type of research used is development research. Research data was analyzed using quantitative and qualitative. Quantitative data is used to measure instrument validity and user response. Meanwhile, qualitative data is used to describe expert responses and research subjects.Thisresearchdatawasanalyzedusingquantitativeandqualitative analysis techniques. The test subjects were VIII grade students atSMP PGRI 01 Pakisaji. The research instruments included: validation sheet,teacher response questionnaire, and learner response questionnaire. The resultsshowed that: (1) the evaluation media is very valid based on media expertassessment of 85.5%, content expert assessment of 90.6%, and practitionerassessment of 96.6%. (2) the developed evaluation media showed high validityand practicability with a teacher response questionnaire reaching 90.4% and astudent response questionnaire reaching 89.5%. Overall, the evaluation mediadeveloped is valid and practical to use in learning the material of the system oflinearequationsof two variables.